Technique of definition of average values definition of kinetic dependences - Погожих, Микола Іванович; Павлюк, Ігор Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
The problem of data processing is considered and developed a technique that allows to automatically determine the average value of any kinetic relations and the centers of flat shapes formed by these dependencies